Mortality Detail File, 1992 ([Verlag nicht ermittelbar], 1997)
This data collection describes every death or fetal death registered in the United States for 1992. Information includes the month of death, day of the week of death, the sex and race of the deceased, the age of the deceased at the time of death, the deceased's place of residence, place of death, and whether an autopsy was performed. Causes of death are coded using THE MANUAL OF THE INTERNATIONAL STATISTICAL CLASSIFICATION OF DISEASES, INJURIES, AND CAUSE-OF-DEATH, NINTH REVISION (ICD-9), VOLUMES 1 AND 2.